SERUM C3 AND SERUM C4 COMPLEMENT IN PATIENTS WITH BURN TRAUMA AND CORRELATION WITH BURN INJURY SEVERITY - Arslanagic, Selma; Karamehic, Jasenko (Sanamed, 2022)
Introduction: Burns, depending on the degree of severity, induce a significant pathophysiological response in the body. The complement system participates in the body's defenses as well as in immune responses after burn-induced trauma.Objectives: The main objective of the study was to examine how burn severity affects serum C3 and serum C4 complement values; whether burn severity correlates with serum C3 and C4 complement, and establish the predictive value of the serum C3 complement and serum C4 complement for assessing the severity of the burn. Patients and methods: According to the degree of TBSA, patients were classified into three groups: group with %TBSA15% -25% (30 patients), and group with %TBSA > 25% to 40% (30 patients). According to the depth of burns, patients were classified into two groups partial-thickness burns (39 patients) and full-thickness burns (51 patients). We followed laboratory parameters: value serum C3 complement and serum C4 complement on the first and seventh day after burn trauma.Results: Serum C3 complement was significantly lower in patients with %TBSA>25%-40% and in the group with %TBSA>15%-25% compared to patients with %TBSA15%-25% compared to patients with %TBSA
Keywords: burns; %TBSA; depth of burns; serum C3 complement; serum C4 complement; predictory significance